Cover-based allometric estimate of aboveground biomass of a non-native, invasive annual grass (Bromus tectorum L.) in the Great Basin, USA. (October 2021) - Mahood, Adam L.; Fleishman, Erica; Balch, Jennifer K.; Fogarty, Frank; Horning, Ned; Leu, Matthias; Zillig, Martha; Bradley, Bethany A.
Abstract: Cheatgrass ( Bromus tectorum L.) presence in the Great Basin is associated with an increase in fire frequency and size, likely due to increased spatial continuity of fine fuel biomass. Measurements of the extent and cover of cheatgrass are steadily improving, but the strength of the relationship between cover and aboveground biomass (AGB) is unclear. An allometric equation that can reliably convert cover to AGB of cheatgrass would allow for improved incorporation of regional estimates of cover into models of fire activity, carbon storage, and net primary productivity, all of which rely on biomass. We measured cover and AGB of cheatgrass at 60 locations in the north-central Great Basin and used these measurements to model the relationship. We found a strong, linear relationship between the percent cover and AGB, which was improved after square root transformation of both cover and AGB, and after incorporating the number of days after peak NDVI that the biomass and cover were measured. These results show that AGB of cheatgrass can be reliably estimated from cover. It is likely that allometric equations based on cover will be effective for other grass species, but care must be taken to account for phenology (e.g., peak NDVI) in the estimation. Highlights: Remotely sensed, regional scale cover estimates exist for cheatgrass. Ground measurements were used to convert cover to aboveground biomass. The relationship is non-linear. Each side of the equation was square-root transformed. There was little Inter-annual variability in the cover-biomass relationship. Intra-annual variability due to senescence was more important to account for.